Tablas y textos de cómputo en códices de San Isidoro de León. El códice IV - Suárez González, Ana (Estudios humanísticos. Geografía, historia y arte, 1993)
The texts relative to the computation and closely connected with me determination of the date of Easter were widespread in the Middle Ages. We can find significative examples of this kind of texts in the twelfth century manuscripts, coming from the scriptorium of San Isidoro of León.